(untitled) (Journal of Geography and Environmental Management, 2016)
WebGIS originates from a combination of web technology and Geographical Information System (GIS) which simplifies the exchange of geographical data, provides structured information for users and to access GIS applications without using any specific software. This article focuses on development and implementation of WebGIS application for the seismicity analysis and earthquake information of Kyrgyzstan. A dynamic map browser was designed on the base of UMN MapServer software which is an open source package. It is a free alternative to other commercial applications, and a good solution when highly customized applications are needed. Implementation of this application provides easy access on the Internet for users to analyze the spatial distribution of geographical and seismic data. This application is very helpful for local population to increase their preparedness where the earthquake losses can be reduced.